If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 17x + -7 = 6(4x + 10) Reorder the terms: -7 + 7x + 17x = 6(4x + 10) Combine like terms: 7x + 17x = 24x -7 + 24x = 6(4x + 10) Reorder the terms: -7 + 24x = 6(10 + 4x) -7 + 24x = (10 * 6 + 4x * 6) -7 + 24x = (60 + 24x) Add '-24x' to each side of the equation. -7 + 24x + -24x = 60 + 24x + -24x Combine like terms: 24x + -24x = 0 -7 + 0 = 60 + 24x + -24x -7 = 60 + 24x + -24x Combine like terms: 24x + -24x = 0 -7 = 60 + 0 -7 = 60 Solving -7 = 60 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| x^2+5x-2x=12-8 | | 0.25x+25=0.50x+15 | | -3.268=0.3k-0.7 | | 0.5x+3=0.75-7.75 | | -5(6k+9)=-27+7k | | 20=20log(x) | | 0.4-0.107= | | 78=1/2h(5+8) | | 5.6x+3=4.6x | | 2x-(6x-4)=8-4x | | 10-7x=-(x-12) | | 16x=-50 | | 3y-20=40 | | 8k-2=4 | | Y^2+3y=x^3-x | | 3w-4=4w | | 18(x+3)=2(9x+2)+50 | | 5b-3=-9 | | 4n+15=4n+15 | | 8x+7(-3x-6)=-52-3x | | 10x+18=3(3x+4) | | -12+5x=3(x+2) | | 5-4=u | | 8x-4(40+x)=4 | | 30x-9=21x-53 | | -2n+3+3-7n= | | 3s+12=-6s+6 | | -1.1+u=8 | | 20x-1=4(5x+6) | | 54=(4x-6) | | 4y-8+y=46+3y-4y | | -12+5x=3(x-2) |